Heteroatom (N or N-S)-Doping Induced Layered and Honeycomb Microstructures of Porous Carbons for CO2 Capture and Energy Applications - Tian, W.; Zhang, H.; Sun, Hongqi; Suvorova, A.; Saunders, M.; Tade, M.; Wang, S. (Wiley, 2016)
Increasing global challenges such as climate change, environmental pollution, and energy shortage have stimulated the worldwide explorations into novel and clean materials for their applications in the capture of carbon dioxide, a major greenhouse gas, and toxic pollutants, energy conversion, and storage. In this study, two microstructured carbons, namely N-doped pillaring layered carbon (NC) and N, S codoped honeycomb carbon (NSC), have been fabricated through a one-pot pyrolysis process of a mixture containing glucose, sodium bicarbonate, and urea or thiourea. The heteroatom doping is found to induce tailored microstructures featuring highly interconnected pore frameworks, high sp2-C ratios, and high surface areas. The formation mechanism of the varying pore frameworks is believed to be hydrogen-bond interactions. NSC displays a similar CO2 adsorption capacity (4.7 mmol g-1 at 0 °C), a better CO2/N2 selectivity, and higher activity in oxygen reduction reaction as compared with NC-3 (the NC sample with the highest N content of 7.3%). NSC favors an efficient four-electron reduction pathway and presents better methanol tolerance than Pt/C in alkaline media. The porous carbons also exhibit excellent rate performance as supercapacitors.